2014
DOI: 10.1093/jscr/rju080
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol sclerotherapy of rectal venous abnormalities in Klippel-Trenaunay syndrome

Abstract: Klippel–Trenaunay syndrome (KTS) is a rare congenital disorder characterized by the triad of capillary malformations, atypical venous malformations and varicosities and bony and/or soft tissue hypertrophy. We present the case of an 18-year-old man with KTS affected by haematochezia secondary to rectal venous malformations that was managed with endoscopic sclerotherapy. In this case, we compared the use of ethanol to phenol as a sclerosant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Sclerotherapy is performed frequently and effectively in the treatment of VMs 19 . Endoscopy-guided hybrid sclerotherapy of colonic VMs may be a viable therapeutic option 5 , but research supporting this treatment is rare and until now has only been described in case reports 20,21 . One study 20 presented two patients who suffered from massive venous malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerotherapy is performed frequently and effectively in the treatment of VMs 19 . Endoscopy-guided hybrid sclerotherapy of colonic VMs may be a viable therapeutic option 5 , but research supporting this treatment is rare and until now has only been described in case reports 20,21 . One study 20 presented two patients who suffered from massive venous malformations.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Embolization of lesions has been performed using a variety of agents, including ethanol. Agostinho et al 12 reported a case of a patient with Klippel-Trenaunay syndrome who had presented with hematochezia resulting in anemia secondary to multiple giant rectal VMs. They reported resolution of hematochezia and a decrease in the size of the large rectal VMs after injection of 75% ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…They reported resolution of hematochezia and a decrease in the size of the large rectal VMs after injection of 75% ethanol. 12 However, they acknowledged a set of major adverse events related to distal embolization, including pulmonary embolism and cardiovascular collapse. 12 We continue to advise against the use of ethanol for the treatment of more voluminous VMs owing to the high rates of serious complications, despite its highly effective therapeutic profile.…”
Section: Discussionmentioning
confidence: 99%